Air sacs and vocal fold vibration: Implications for evolution of speech - De Boer, Bart (Theoria et Historia Scientiarum, 2012)
Interaction between vocal fold vibration and the vocal tract was modeled for vocal tracts with air sacs, and it was investigated how the properties of the upper vocal tract influence the regularity of vocal fold vibration. It was found that for constant vocal tract shape, a first determinant of whether voicing was irregular was lung pressure. Although it appears that in general the larger the lung pressure, the more likely it is that vocal fold vibration becomes irregular, this is certainly not a simple relationship: there were cases of low lung pressure with irregular voicing as well as cases of high lung pressure with regular voicing for both soft and hard-walled air sacs, and for vocal tracts without air sacs.